Pengaruh waktu pendinginan dan pembekuan terhadap suhu pusat dan nilai total plate count produk shrimp roll di PT XYZ - Iza Fauziah Hasan; Ai Imas Faidoh Fatimah (Yayasan Baru Haji Samsudin, 2026)
Frozen shrimp roll is a high-risk processed food product that requires strict temperature control during production to ensure product quality and safety. Failure to achieve optimal cooling and freezing temperatures may lead to quality deterioration and increase the risk of microbial growth. This study aimed to evaluate the effects of cooling time and freezing time on the core temperature and microbiological quality of shrimp roll. A factorial completely randomized design was employed with two factors: cooling time (24, 28, and 32 min) and freezing time (30, 35, 40, and 45 min), each conducted in duplicate. The observed parameters included product core temperature and Total Plate Count (TPC). The results showed that freezing time significantly affected (p < 0.05) the core temperature of shrimp roll, whereas cooling time had no significant effect. However, the interaction between cooling time and freezing time significantly influenced the product’s core temperature. The lowest core temperature achieved was −28.35°C at a cooling time of 32 min and a freezing time of 45 min. Considering both target temperature attainment and process efficiency, the combination of 24 min cooling and 40 min freezing was identified as the optimum treatment, resulting in a core temperature of −23.05°C. TPC analysis revealed that all treatments yielded microbial counts of <1.0 × 10³ CFU/g, which were below the maximum limit established by PT XYZ. These findings indicate that the applied cooling and freezing conditions were effective in achieving the required core temperature while maintaining the microbiological quality of shrimp roll.